Classification of Chronic Hydrocephalus in Adults: A Systematic Review and Analysis - Mats Tullberg; Ahmed K. Toma; Shigeki Yamada; Katarina Laurell; Masakazu Miyajima; Laurence Watkins; Carsten Wikkelsø (2023)
Chronic hydrocephalus in adults (CHiA) includes all nonacute forms of hydrocephalus occurring in adulthood. It covers a spectrum of disorders. Some of these have relatively agreed on definitions, while others are less well characterized. The existing medical classification systems lack adequate structure and are neither clinically oriented nor easy to use, which severely hampers research and clinical care efforts.